Assessment processes for sustainability and sustainable development - Erickson, Larry E.; Leven, Blase; Saulters, Oral; Boguski, Terrie; Green, Ryan (Kansas State University, 2011)
There is a growing emphasis to include sustainability in decisions that are made, especially in capital investments and strategic planning. The interdisciplinary tools and approaches of sustainability science are providing an essential framework for strategic planning, process design, problem solving, and decision making across systems, sectors, and scales. Sustainability assessments that encompass quantifying ecosystem services, product life cycles, and potential impacts are being integrated into leadership decision making. Governments, corporations, organizations, schools, and communities have all endeavored to establish indicators and metrics for measuring progress toward sustainability goals. Although sustainability initiatives may have moved from the voluntary realm into the “regulatory” universe in some capacities with demands from customers, shareholders, stakeholders, insurers, and government agencies there are many unknowns in this fertile transdisciplinary field of study. The results of a literature review of sustainability indices and assessment processes will be presented.
Keywords: Sustainability; Assessment; Metrics; Ecosystems